The Effect of Workload and Job Characteristics on Employee Performance with Job Satisfaction as a Mediation Variable at the Police Academy - Aiddin Mufti; Tristiana Rijanti (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the influence of workload and job characteristics on employee performance, with job satisfaction as a mediating variable at the Police Academy. Increasing organizational demands require employees to perform optimally, making workload management and job characteristic design crucial factors in improving employee satisfaction and performance. This study employed a quantitative approach with a survey method. The population was all Police Academy employees, with purposive sampling used. Data were collected through questionnaires that had been tested for validity and reliability and then analyzed using path analysis with the aid of SPSS software. The results showed that workload and job characteristics significantly influenced employee job satisfaction and performance. Furthermore, job satisfaction was shown to significantly mediate the effect of workload and job characteristics on employee performance. These findings indicate that proportional workload management and appropriate job characteristic design can enhance job satisfaction, ultimately impacting employee performance at the Police Academy